Plasma bile acids show a positive correlation with body mass index and are negatively associated with cognitive restraint of eating in obese patients - Prinz, Philip; Hofmann, Tobias; Ahnis, Anne; Elbelt, Ulf; Goebel-Stengel, Miriam; Klapp, Burghard F.; Rose, Matthias; Stengel, Andreas (Frontiers in Neuroscience, 2015)
Bile acids may be involved in the regulation of food intake and energy metabolism. The aim of the study was to investigate the association of plasma bile acids with body mass index (BMI) and the possible involvement of circulating bile acids in the modulation of physical activity and eating behavior. Blood was obtained in a group of hospitalized patients with normal weight (BMI 18.5-25 kg/m2), underweight (anorexia nervosa, BMI <17.5 kg/m2) and overweight (obesity with BMI 30-40, 40-50 and >50 kg/m2, n=14-15/group) and plasma bile acid concentrations assessed. Physical activity and plasma bile acids were measured in a group of patients with anorexia nervosa (BMI 14.6±0.3 kg/m2, n=43). Lastly, in a population of obese patients (BMI 48.5±0.9 kg/m2, n=85), psychometric parameters related to disordered eating and plasma bile acids were assessed. Plasma bile acids showed a positive correlation with BMI (r=0.26, p=0.03) in the population of patients with broad range of BMI (9-85 kg/m2, n=74). No associations were observed between plasma bile acids and different parameters of physical activity in anorexic patients (p>0.05). Plasma bile acids were negatively correlated with cognitive restraint of eating (r=-0.30, p=0.008), while no associations were observed with other psychometric eating behavior-related parameters (p>0.05) in obese patients. In conclusion, these data may point towards a role of bile acids in the regulation of body weight. Since plasma bile acids are negatively correlated with the cognitive restraint of eating in obese patients, this may represent a compensatory adaptation to prevent further overeating.